How perceived educational and social support influence entrepreneurial intentions in music majors: A mediated moderation model with music entrepreneurship motivation and gender - Jing, Feng; Hamid, Junainah Abd; Tham, Jacquline (Edelweiss Applied Science and Technology, 2025)
With the vigorous development of the world economy, countries worldwide are trying to enhance the quality of entrepreneurship education. By incorporating the art of music into the entrepreneurship education curriculum, students are exposed to the essence of human culture while developing their understanding and practical skills in innovation and creativity. This approach to education not only helps students make meaningful contributions to a vibrant arts community in the future but also inspires their multicultural awareness and global outlook. Previous studies have shown that entrepreneurial prospects for Chinese college students are not promising. In the field of academic education, there are disadvantages to the entrepreneurial education ecosystem, such as the lack of strong external support factors. Regarding entrepreneurial motivation, their drive is often confined to simple financial gain, with insufficient psychological readiness and a dearth of social networks posing challenges to their entrepreneurial endeavors, thereby impeding their engagement in such activities. This study selected 470 music students from nine universities in Sichuan as research participants. The study used a cross-sectional survey design, and the participants completed an online questionnaire designed by the researchers. This study employed quantitative research methods, utilizing SPSS and AMOS for data analysis. A stratified random sampling technique was applied to perform a comprehensive descriptive analysis of the questionnaire data.